The success of the Ibero-American Summit of Cádiz - Siles del Valle, Juan Ignacio (Razón y fe, 2018)
After the relative failure of the Summits of Mar de la Plata and Asunción, that of Cádiz can be considered successful. Brazil, the already giant emerging country, and Spain, each in their own way, led the Summit and advocated for a new conception and practice of multilatin relations and for the return of credit to the wounded economies of Spain and Portugal.